Enhanced Attenuation and Bandwidth of Electromagnetic Absorbers Through Monte Carlo Optimization of Resonant Periodic Metastructures - Steven Mamolo; Dandan Zhang; Kanat Anurakparadorn; Eric Michielssen; Alan Taub (My University, 2025)
Modern aerospace systems require robust electromagnetic interference (EMI) mitigation techniques to ensure the reliability of critical electronics used in data exchange, threat detection, and flight navigation and control. This study introduces a method for designing lightweight electromagnetic absorbers using resonant periodic metastructures. Monte Carlo simulation was employed to optimize the attenuation and bandwidth of an engineered porous polymer nanocomposite in the X-band frequency range (8–12 GHz). Simulated for a rectangular waveguide operating in transverse electric mode TE10, the optimized absorber achieved a minimum reflection loss (RL) of -37 dB and operational bandwidth (OBW, bandwidth at -20 dB) of 1.1 GHz. Experimental validation resulted in a minimum RL of -34 dB and OBW of 0.66 GHz. This is a substantial improvement over the baseline material, which required 50% more volume and weight to achieve a minimum RL of -19 dB. These findings highlight the potential of periodic metastructures for lightweight EMI absorber applications.
Keywords: Advanced Antenna and Metasurface Technologies; Metamaterials and Metasurfaces Applications; Electromagnetic wave absorption materials